Crash behaviour of a carbon fibre floor panel. (11th May 2007) - Carrera, M.; Cuartero, J.; Miravete, A.; Jergeus, J.; , Kaj Fredin
The engineering design of a floor pan structure to meet existing requirements on torsion and bending stiffness of a reference steel floor while reducing its weight by 50% and the number of parts by 70% is discussed here. The crashworthiness of the composite floor pan design is evaluated by means of the commercial PAMCRASH explicit Finite Element software package by reproducing the same loading and support conditions of the EuroNCAP pole side impact crash test. The numerical results are then compared against the experimental data from two crash tests and the results confirm that a good degree of confidence can be used in the numerical simulation of the crash behaviour of textile composites.